Diversifikasi Pengolahan Gula Kelapa Di Desa Sungai Intan Kecamatan Tembilahan Hulu Kabupaten Indragiri Hilir - Nursida; I.Sari; Marlina; Y.Riono; E.Y.Yusuf; M.Arfah (Indra Institute Research & Publication, 2023)
This community service activity was carried out at Sumgai Intan, Tembilahan Hulu District, with the aim of increasing the community's knowledge and skills regarding the diversification of coconut sugar processing. The method used in this activity is counseling and followed by discussions with the village community as a process for transferring knowledge. The main target groups are coconut sugar craftsmen, coconut farmers, farmer/women groups, PKK activists and school dropout youth. Evaluation of the results of counseling is carried out after counseling and discussions have been carried out. The results of community activities show that the implementation of training and diversification of coconut sugar processing diversification in Sungai Intan Village, Tembilahan Hulu District, Indragiri Hilir Regency has been able to increase the knowledge and skills of training participants in processing natural resources in Sungai Intan Village, namely coconuts by diversifying yields. processed coconut sugar both in solid liquid and crystal form. The success of the training and socialization through this extension program is also seen to be able to encourage the growth of creative and innovative ideas as well as the entrepreneurial spirit of the training participants and the people of Sungai Intan Village. This service is carried out as one of the village programs to increase the community's ability to process various forms of coconut sugar to increase farmers' income